Translators’ Professionalism and the Status of Translation as a Profession in the Mid- and late-nineteenth Century Iran - Atefmehr, Zahra (chronotopos – A Journal of Translation History, 2023)
The nineteenth century was the era of reform and gradual move to modernization in Iran. In such a milieu, translation provided an efficient means to access the knowledge and science of Europe, which was the epitome of success and prosperity for the Iranian intellectuals. In the mid-nineteenth century, when Naser al-Din Shah (r. 1848-1896) ascended the Qajar throne, his deep absorption in the West and his strong passion for learning about Europe and for modernization of the country brought about a dramatic increase in translation activity. In the fifty-year ruling period of Naser al-Din Shah, i.e., the mid- and late-nineteenth century Iran, translation offices were established and translators were widely employed in different institutions by the government. Using primary sources and documents, this archival research first examines the role of Naser al-Din Shah in production and publication of translations, then it explores whether translation was a profession in Iran in the mid- and late-nineteenth century or not and finally, it tries to find out if translators of the Naseri era can be considered professionals or not. Adopting two definitions as a yardstick, the study concludes that translation activity in the mid- and late-nineteenth century Iran had some characteristics that allow us to call it a profession. The study also argues that given the historical context of Iran in that era, the translators held the basic qualifications to be considered semi-professionals, while among them some were highly professional.